2012
DOI: 10.1017/s0047279412000220
|View full text |Cite
|
Sign up to set email alerts
|

Re-conceptualising Approaches to Meeting the Health Needs of Homeless People

Abstract: The experience of homelessness not only affects physical health, but can also constrain access to required health care. In a number of European countries, national strategies to tackle homelessness have sought to deliver integrated solutions across housing, health and other social policy areas. This article examines approaches to meeting the health care needs of homeless people in relation to such strategies, drawing upon recent research in Norway and Scotland. The article presents a comparative analysis of ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 9 publications
1
26
0
Order By: Relevance
“…However, many people with experience of homelessness report that their needs are not well met when accessing mainstream health or substance use services. Stigmatising and negative attitudes also, unfortunately, remain commonplace [21,[42][43][44]. For those who have successfully engaged with treatment, there can be distinct challenges associated with continued engagement with treatment and recovery as a result of being homeless.…”
Section: Treatment For Problematic Substance Usementioning
confidence: 99%
“…However, many people with experience of homelessness report that their needs are not well met when accessing mainstream health or substance use services. Stigmatising and negative attitudes also, unfortunately, remain commonplace [21,[42][43][44]. For those who have successfully engaged with treatment, there can be distinct challenges associated with continued engagement with treatment and recovery as a result of being homeless.…”
Section: Treatment For Problematic Substance Usementioning
confidence: 99%
“…As might be expected, access to general health services appears to be most universal in the Nordic states. For example, in Norway, any specialist health care services tend to be provided on the basis of health care need (such as for substance use) rather than because of any homelessness status (Anderson and Ytrehus, 2012). Similarly, in Slovenia research indicated that the majority of homeless persons found health care services accessible (Razpotnik & Dekleva 2009a, b).…”
Section: Access To Health Services For Homeless Womenmentioning
confidence: 99%
“…In an international review, Pleace and Quilgars (2004) identified adaptations to exiting services, specialist primary care services, and specialist complementary services (for example, alcohol and drug support, dentistry, podiatry, and opticians): but found limited evaluative evidence of their effectiveness. There has been considerable debate around the necessity of specialist services compared to the need to better ensure homeless people's inclusion in mainstream services (Anderson et al, 2006;FEANTSA 2006FEANTSA , 2011Joly et al, 2011;Jones and Pleace, 2010;O'Carroll and O'Reilly, 2008), with Anderson and Ytrehus (2012) concluding that specialist health care provision for homeless people should be transitional and ultimately designed to aid reintegration into mainstream services.…”
Section: Access To Health Services For Homeless Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…While housing may be largely distributed through the market, homelessness interventions are rarely, if ever, delivered by market mechanisms (though they may reflect market failure). Comparative homelessness research has often used welfare state regimes as a background typology (Anderson & Ytrehus, 2012;Baptista & O'Sullivan, 2008;Benjaminsen et al, 2009) and there is some consensus that homelessness to some extent reflects welfare state regimes, the degree of decommodification of welfare and the generosity of welfare spending. Nordic welfare states would be characterised as least commodified/most generous, with the Southern European countries at the opposite end of the spectrum.…”
Section: Institutions and Homelessnessmentioning
confidence: 99%